Graphical wireless medium access control (MAC) protocol simulator - Tan, Shermin Weixiu (2014)
Paper documents and PowerPoint presentations do not provide an interactive platform for keen learners to learn the concepts of the Medium Access Control (MAC) protocol, Carrier Sense Multiple Access/ Collision Avoidance (CSMA/CA) for IEEE 802.11 Standard. Thus, this project proposed and developed an online graphical simulator, where the theories of MAC protocol were integrated into the program. Through the program, users can indicate the parameters they want the nodes to contain, and the graphical simulator will draw the associated timelines at real time. Pop-outs containing explanations of the states that the nodes are going through are also created along the timelines. This is to guide program users in understanding the display of that particular state at that particular time. MAC concepts and theories were studied thoroughly by the author, before coming up with the calculations and algorithms involved, in devising and implementing each timeline state. Research on the MAC protocol performance using the developed graphical simulator or on an improvised version, is recommended as part of the project’s future work.